The mediating role of self-esteem in the relationship between family functioning and symptoms of eating disorder in adolescents during home quarantine duo to coronavirus (COVID-19) - Gholami hosnaroudi, Motahareh; Kachooei, Mohsen; Fatehi, Nazanin (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The present study aimed to determine the mediating role of self-esteem in the relationship between family functioning and symptoms of eating disorder in adolescents during home quarantine duo to COVID-19. Methods: The research method was descriptive-correlational, and the statistical population consisted of all students aged 13 to 18 years in Tehran in the academic year of 2019-2020. Among them, 384 individuals were selected by convenient sampling method. Family functioning Questionnaire (Faces-III) by Olson (1986), Eating Disorders Diagnostic Scale (EDDS) by stice et al (2000), and self-esteem scale (RSES) by Rosenberg (1965) were used to measure the variables. Data were analyzed through mediation analysis using AMOS software. Results: The results of the mediation analysis showed that the direct effect of family functioning on symptoms of eating disorder was significant (p